Database and expert systems applications 22nd International Conference, DEXA 2011, Toulouse, France, August 29 - September 2, 2011. Proceedings, Part I - Hameurlain, Abdelkader; Liddle, Stephen W.; Schewe, Klaus-Dieter; Zhou, Xiaofang (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 22 International Conference on Database and Expert Systems Applications, DEXA 2011, held in Toulouse, France, August 29 - September 2, 2011. The 52 revised full papers and 40 short papers presented were carefully reviewed and selected from 207 submissions. The papers are organized in topical sections on query processing; database semantics; skyline queries; security and privacy; spatial and temporal data; semantic web search; storage and search; web search; data integration, transactions and optimization; and web applications.